Integrated Design-to-Validation Framework for a Precision Dovetail Clamping Fixture in CNC Machining Applications - Adam Satria; Aditya Al Fathir; Adrian Satriatama; Ahmad Rifai; Ardytya P. I. Sukardi; Hilmi Yudhistira; Maulana H. Rohman (Infotekmesin, 2026)
Conventional vise-based workholding systems in CNC machining often limit tool accessibility, provide non-uniform clamping forces, and reduce machining stability. While dovetail clamping mechanisms have been widely investigated, studies integrating fixture design, manufacturing, experimental validation, and structural analysis into a practical and cost-effective solution remain limited. This study develops and validates a precision dovetail clamping fixture for CNC milling applications. The proposed fixture combines parametric CAD-based design, CNC manufacturing using S50C steel, experimental validation, and static structural simulation. Experimental results demonstrated dimensional accuracy within ±0.05 mm, improved workpiece accessibility, and minimal displacement during machining. Structural simulation under representative clamping and machining loads yielded a maximum von Mises stress of 188 MPa, a maximum displacement of 0.645 mm, and a minimum factor of safety of 2, indicating safe operation within the elastic range of the material. The developed fixture provides a reliable, economical, and practical alternative for precision CNC machining in small-scale industrial environments..